Guidelines versus practice in screening and monitoring of cardiometabolic risks in patients taking antipsychotic medications: where do we stand? - Azfr Ali, Ruba Saleh; Jalal, Zahraa; Paudyal, Vibhu (General psychiatry, 2021)
Antipsychotic-induced adverse cardiometabolic effects, such as weight gain, high blood pressure, alterations in glucose metabolism and lipid dysregulation, are well-recognised risk factors for cardiovascular diseases (CVDs) and diabetes.1 Clinical guidelines call for regular physical health assessments and laboratory monitoring as a means to prevent and detect adverse cardiometabolic effects of antipsychotic medications. Suboptimal cardiometabolic screening among antipsychotic users can hinder the early detection of high-risk people and delay receiving proper management.2 Antipsychotic medications and adverse cardiometabolic effects Although the pathophysiological pathways underlying cardiometabolic side effects of antipsychotic treatment are not fully understood, antipsychotic-induced cardiometabolic side effects are attributed to multiple functional pathways. [...]clozapine, olanzapine, risperidone and quetiapine have been recognised as the antipsychotics with the highest metabolic liability. [...]evidences suggest that some antipsychotics, mainly aripiprazole and ziprasidone, demonstrate neutral cardiometabolic effects. Specifically, the recommendations include monitoring of factors such as personal and family history, anthropometric measures and body compositions (weight, body mass index (BMI), waist circumference (WC) and blood pressure (BP)), fasting plasma glucose (HbA1c) and lipid profile.4 Similarly, international clinical guidelines on the same subjects were introduced4 5 7–12 (table 1).Table 1 Guidelines for cardiometabolic risk factor monitoring in patients treated with antipsychotic medications Guideline Origin Focus of the guideline Recommended cardiometabolic components Consensus Statement on Antipsychotic Drugs and Obesity and Diabetes7 USA Monitoring of metabolic adverse events associated with antipsychotics Focusing mainly on SGAs Physical health monitoring: anthropometrics and body compositions (BP, WC and BMI) Biochemical examination: fasting glucose and lipids Baseline follow-up: 4–8 weeks, quarterly, then annually Monitoring for Metabolic Disorders in Patients Taking Antipsychotic Drugs8 New Zealand Monitoring of metabolic adverse events associated with antipsychotics Physical health monitoring: body compositions (body weight and BMI) Biochemical examinations: fasting glucose and lipids Cardiovascular examination: ECG Baseline follow-up: quarterly, then annually (frequency increased in high-risk groups) World Federation of Societies of Biological Psychiatry Guidelines for Biological Treatment of Schizophrenia9 Global Management of schizophrenia and related disorders General recommendations including general health monitoring Physical health monitoring: anthropometrics and body compositions (BP, body weight, WC and BMI) Biochemical examinations: fasting glucose and lipids Cardiovascular examination: ECG Baseline follow-up: 4–8 weeks, quarterly, then annually Personal/family history (lifestyle and smoking) NICE Guidelines: Psychosis and Schizophrenia in Adults4 UK Management of schizophrenia and related disorders Evidence-based recommendations for optimising treatment and prognosis General recommendations including general health monitoring Personal/family history (lifestyle and smoking) Physical health monitoring: anthropometrics and body compositions (BP, body weight, WC and BMI) Biochemical examination: fasting glucose and lipids Baseline follow-up: 4–6 weeks, quarterly, then annually The Royal Australian and New Zealand College of Psychiatrists Guidelines for the Management of Schizophrenia and Related Disorders10 Australia and New Zealand Management of schizophrenia and related disorders General recommendations including general health monitoring Focusing mainly on SGAs Physical health monitoring: anthropometrics and body compositions (BP, body weight, WC and BMI) Biochemical examination: fasting glucose and lipids Managing any existing metabolic comorbidities The Maudsley Prescribing Guidelines in Psychiatry11 UK Evidence-based recommendations for optimising treatment and prognosis General recommendations including general health monitoring Physical health monitoring: anthropometrics and body compositions (BP, body weight, WC and BMI) Biochemical examination: fasting glucose and lipids Cardiovascular examination: ECG Early on-treatment monitoring: during dose titration Baseline follow-up: quarterly, then annually SIGN Guidelines: Management of Schizophrenia5 Scotland Evidence-based recommendations for optimising treatment and prognosis General recommendations including general health monitoring Personal/family history (lifestyle and smoking) Physical health monitoring: anthropometrics and body compositions (BP, body weight, WC and BMI) Biochemical examination: fasting glucose and lipids Pretreatment screening Baseline follow-up: quarterly, then annually BMI, body mass index; BP, blood pressure; ECG, electrocardiogram; NICE, National Institute for Health and Care Excellence; SGAs, second generation antipsychotics; SIGN, Scottish Intercollegiate Guidelines Network; WC, waist circumference.